2013
DOI: 10.1093/hmg/ddt083
|View full text |Cite
|
Sign up to set email alerts
|

KBP–cytoskeleton interactions underlie developmental anomalies in Goldberg–Shprintzen syndrome

Abstract: Goldberg-Shprintzen syndrome (GOSHS, MIM #609460) is an autosomal recessive disorder of intellectual disability, specific facial gestalt and Hirschsprung's disease (HSCR). In 2005, homozygosity mapping in a large consanguineous family identified KIAA1279 as the disease-causing gene. KIAA1279 encodes KIF-binding protein (KBP), whose function is incompletely understood. Studies have identified either the mitochondria or the cytoskeleton as the site of KBP localization and interactions. To better delineate the KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 47 publications
2
36
1
Order By: Relevance
“…Previous studies have provided evidence both for and against an essential role for neurites in ENCC migration. Humans with mutations in the gene encoding kinesin binding protein (KBP) have Hirschsprung disease [68], and studies in neuronal cell lines, primary cortical neurons and zebrafish have shown that the main role of KBP appears to be in neurite formation [69-71]. On the other hand, mutant mice with defects in the longitudinal projections of neurites do not exhibit any delay in ENCC migration [38] showing that longitudinal neurite projections are not essential, or that only a small number of longitudinally oriented neurites is necessary, for normal ENCC migration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided evidence both for and against an essential role for neurites in ENCC migration. Humans with mutations in the gene encoding kinesin binding protein (KBP) have Hirschsprung disease [68], and studies in neuronal cell lines, primary cortical neurons and zebrafish have shown that the main role of KBP appears to be in neurite formation [69-71]. On the other hand, mutant mice with defects in the longitudinal projections of neurites do not exhibit any delay in ENCC migration [38] showing that longitudinal neurite projections are not essential, or that only a small number of longitudinally oriented neurites is necessary, for normal ENCC migration.…”
Section: Discussionmentioning
confidence: 99%
“…A gene panel was designed to include 31 genes that were reportedly related to HSCR or ENCCs development and migration in the literature. The genes were selected due to their direct involvement in or indirect interaction with the RET_GDNF pathway; the EDNBR_EDN3 pathway; the ENCC proliferation, migration or differentiation; or an association with HSCR ever reported in the literature with or without definite mechanisms explained . (Table ) All the genes were sequenced in full‐length except for NRG3 , which was sequenced for exons only due to its enormous size.…”
Section: Methodsmentioning
confidence: 99%
“…Our study identifies KBP as a novel marker for the late CB. Contradictory results have also been published about the direct interaction of KBP with the cytoskeleton (Alves et al 2010, Drevillon et al 2013. Drevillion et al reports KBP interaction with both tubulin and F-actin, hypothesizing KBP contribution in cross-linking microtubules and F-actin cytoskeleton, but the interaction with tubulin was not detected by Alves et al Whether the interaction with microtubules is direct or mediated by other proteins, KBP appears to have a central role in the microtubule-mediated functions and microtubule dynamics.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported to colocalize with the mitochondria in NIH3T3 cells and to affect mitochondrial distribution by binding to the carboxylterminal region of the motor domain of KIF1B and improving its motility (Wozniak et al 2005). However, mitochondrial localization was not observed in human fibroblasts (Alves et al 2010, Drevillon et al 2013 or Hela cells (Alves et al 2010), therefore leaving the mitochondrial role of KBP to be confirmed. Mutations in the Kbp gene have been shown to cause defects in the enteric and central nervous system and to cause the Goldberg-Shprintzen syndrome (GOSHS) in humans (Brooks et al 2005).…”
Section: Introductionmentioning
confidence: 99%